Five cases of missed cystic fibrosis heterozygous mutations identified after a positive newborn screen on a sibling. (2022) - Qussous, Khaleel; Abdulhamid, Ibrahim; Kleyn, Mary; Schuen, John; Nasr, Samya Z.
Abstract: In Michigan (MI), NBS for CF was started in October 2007 using the IRT/DNA protocol. In 2016, a component of the Hologic molecular test kit used by the MI NBS lab was recalled (40 CF mutation 2nd tier test). This recall had a major impact on states using the Hologic test kits in their NBS programs. Michigan specimens were sent to another state's NBS Lab for 2nd tier testing using the Luminex 60 mutation test kit until the Luminex kit could be procured and validated in MI. In this report, we present five cases born during this time period. These cases were initially reported out as having normal NBS results for CF but had heterozygous F508 del (c.1521_1523delCTT) mutations later identified. Of the five cases, one was diagnosed with CF (Case1), one with CF related metabolic syndrome (CRMS), and the other three were carriers.